Surface morphology and mechanical strength of AISI M2 tool steel treated in abnormal glow region of plasma - Naz, M.Y. (Allerton Press Incorporation, 2015)
Plasma ion nitriding is a flexible and multi-functional casehardening technique used in the given study for surface modifications of AISI M2 tool steel (0.9 C, 4.2 Cr, 5.0 Mo, 6.0 W, and 2.0 V). By varying the plasma treatment time from 1 to 4 hour and the filling gas pressure from 1 to 4 mbar, the surface nitriding was carried out in the abnormal glow region of a pulsed DC discharge. Pre-plasma treatment heating of the samples was performed by a heating unit; the substrate temperature was raised to 500Â°C, with the ramping rate of 15Â°C. The resultant microscopic changes in the surface properties of the plasma treated tool steel were studied with different surface characterization techniques such as X-ray Diffraction, Scanning Electron Microscopy and Vickersâs micro-hardness testing. These investigations confirmed the formation of a compound layer on the plasma exposed surface. It was observed that the layer thickness initially increases and then decreases with nitriding time. Similar results were obtained for increasing filling gas pressure. The X-ray Diffraction results showed a down-shift in the original diffraction peaks, which confirms the nitrogen diffusion into the exposed surface and a compound layer formation. A significant improvement in the surface hardness was also vivid, which might be due to the nitrogen diffusion and the formation of a compound layer on the target surface. Â© 2015, Allerton Press, Inc.